SARS-CoV-2 Infection Triggers Phosphorylation: Potential Target for Anti-COVID-19 Therapeutics - Chatterjee, Bhaswati; Thakur, Suman S. (Frontiers in Immunology, 2022)
The SARS-CoV-2 infection triggers host kinases and is responsible for heavy phosphorylation in the host and also in the virus. Notably, phosphorylations in virus were achieved using the host enzyme for its better survival and further mutations. We have attempted to study and understand the changes that happened about phosphorylation during and post SARS-CoV-2 infection. There were about 70 phosphorylation sites detected in SARS-CoV-2 viral proteins including N, M, S, 3a, and 9b. Further, more than 15,000 host phosphorylation sites were observed in SARS-CoV-2 infected cells. SARS-CoV-2 affects several kinases including CMGC, CK2, CDK, PKC, PIKFYVE, and EIF2AK2. Further SARS-CoV-2 regulates various signaling pathways including MAPK, GFR Signaling, TGF-β, autophagy, and AKT. These elevated kinases and signaling pathways can be potential therapeutic targets for anti-COVID-19 drug discovery. Specific inhibitors of these kinases and interconnected signaling proteins have great potential to cure the COVID-19 patients and slow down the ongoing pandemic COVID-19.